Giant Pseudoaneurysm of the Splenic Artery - Gupta, Vishal; Kumar, Sunil; Kumar, Pankaj; Chandra, Abhijit (JOP. Journal of the Pancreas, 2011)
Context Visceral artery pseudoaneurysms are uncommon. They most commonly affect the splenic artery and are secondary to chronic pancreatitis. Giant pseudoaneurysms (5 cm or larger in size) are rare and, until now, only 19 cases have been reported. Case report A 47-year-old chronic alcoholic and diabetic male presented with upper abdominal pain of 1-month duration without any other significant complaint. Computed tomography was performed which revealed features of chronic pancreatitis along with a splenic artery pseudoaneurysm measuring 7x4 cm in size. As the disease was confined to the body and tail of the pancreas, the patient underwent a distal pancreatectomy and splenectomy along with resection of the pseudoaneurysm with an uneventful postoperative course. Conclusion Splenic artery pseudoaneurysms, especially the giant variety, are uncommon. As they are most commonly secondary to chronic pancreatitis, they are better managed surgically which resolves the pseudoaneurysm as well as its underlying cause (i.e. chronic pancreatitis). Image: Pseudoaneurysm with a thin wall.